2022
DOI: 10.3390/ijerph19063156
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmacists-Led Interventions in Primary Care for Adults with Type 2 Diabetes on HbA1c Levels: A Systematic Review and Meta-Analysis

Abstract: Type 2 diabetes mellitus (T2D) is responsible for an important premature mortality. Pharmacists involved in community-based pharmaceutical care services could help patients with diabetes through education and management as they participate in their regular and long-term care. This meta-analysis aimed to evaluate the association between interventions led by pharmacists in the primary care setting and mean change in HbA1c levels. Randomized controlled trials and quasi-experimental studies with a control group we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Similar results were shown in a systematic review, stating that education, medication management and counseling by pharmacists were good, effective methods in improving HbA1c levels [47]. Indeed, a meta-analysis by Coutureau et al also found that the interventions led by pharmacists in primary settings could improve glycemic levels for type 2 diabetes patients through education and management of their therapy [48].…”
Section: Discussionsupporting
confidence: 61%
“…Similar results were shown in a systematic review, stating that education, medication management and counseling by pharmacists were good, effective methods in improving HbA1c levels [47]. Indeed, a meta-analysis by Coutureau et al also found that the interventions led by pharmacists in primary settings could improve glycemic levels for type 2 diabetes patients through education and management of their therapy [48].…”
Section: Discussionsupporting
confidence: 61%
“…The solutions outlined by pharmacists in this survey—enhancing knowledge about therapeutic nutrition and developing private counseling spaces in pharmacies—are in line with earlier research. According to a systematic review of research on the benefits of pharmacy-based interventions on patient nutrition-related outcomes, 32 , 33 pharmacist-led interventions such as nutrition education and counseling can dramatically enhance patient nutrition habits.…”
Section: Discussionmentioning
confidence: 99%
“…A review by Rutter et al 15 from 20 studies concluded that drug information service affects patient outcomes positively. Previous studies and a review article also shows that pharmaceutical care intervention, which includes providing medication information to patients with T2DM, had a positive impact on clinical outcome [16][17][18] . A study in France shows that tailored information about the disease, diet, and drug treatment improved patients' HbA1c levels 19 .…”
Section: Effect Of Drug Information Service On Clinical Outcome Of Pa...mentioning
confidence: 91%